Basic Guide for the Backyard Chicken Flock - Derek L. Barber (EDIS)
AN239, a 4-page illustrated fact sheet by Derek L. Barber, provides basic information for small-farm owners about brooding, housing, feed and water, nesting, breeds of chickens, and hatcheries, for starting a backyard flock. Published by the UF Department of Animal Science, April 2010.